Event detection using sensor networks - Michaelides, Michalis P.; Panayiotou, Christos G. (My University, 2006)
This paper investigates the use of a sensor network for detecting the presence of an event. The sensors monitor the signal emitted from the source and report the existence of the event when the received signal strength is above a certain threshold. In this paper we derive analytical expressions for the probability of false alarms and the probability of no detection as functions of the threshold. Subsequently, we determine the optimal threshold that trades off the probability of false alarms and the probability of no detection. © 2006 IEEE.
Keywords: Event detection; Wireless sensor networks; Acoustic measurements; Radar detection; Acoustic sensors; Cost function; Sensor fusion; Position measurement; Working environment noise; Acoustic signal detection